Schisandra chinensis regulates drug metabolizing enzymes and drug transporters via activation of Nrf2-mediated signaling pathway - He JL; Zhou ZW; Yin JJ; He CQ; Zhou SF; Yu Y (Dove Medical Press, 2014)
Jin-Lian He,1 Zhi-Wei Zhou,2,3 Juan-Juan Yin,2 Chang-Qiang He,1 Shu-Feng Zhou,2,3 Yang Yu1 1College of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 2Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 3Guizhou Provincial Key Laboratory for Regenerative Medicine, Stem Cell and Tissue Engineering Research Center and Sino-US Joint Laboratory for Medical Sciences, Guiyang Medical University, Guiyang, Guizhou, People’s Republic of China Abstract: Drug metabolizing enzymes (DMEs) and drug transporters are regulated via epigenetic, transcriptional, posttranscriptional, and translational and posttranslational modifications. Phase I and II DMEs and drug transporters play an important role in the disposition and detoxification of a large number of endogenous and exogenous compounds. The nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a critical regulator of a variety of important cytoprotective genes that are involved in disposition and detoxification of xenobiotics. Schisandra chinensis (SC) is a commonly used traditional Chinese herbal medicine that has been primarily used to protect the liver because of its potent antioxidative and anti-inflammatory activities. SC can modulate some DMEs and drug transporters, but the underlying mechanisms are unclear. In this study, we aimed to explore the role of Nrf2 in the regulatory effect of SC extract (SCE) on selected DMEs and drug transporters in human hepatocellular liver carcinoma cell line (HepG2) cells. The results showed that SCE, schisandrin A, and schisandrin B significantly increased the expression of NAD(P)H: Nicotinamide Adenine Dinucleotide Phosphate-oxidase or:quinone oxidoreductase 1, heme oxygenase-1, glutamate–cysteine ligase, and glutathione S-transferase A4 at both transcriptional and posttranscriptional levels. Incubation of HepG2 cells with SCE resulted in a significant increase in the intracellular level of glutathione and total glutathione S-transferase content. SCE significantly elevated the messenger ribonucleic acid and protein levels of P-glycoprotein and multidrug resistance-associated protein 2 and 4, whereas the expression of organic anion transporting peptide 1A2 and 1B1 was significantly downregulated by SCE. Knockdown of Nrf2 by small interfering ribonucleic acid attenuated the regulatory effect of SCE on these DMEs and drug transporters. SCE significantly upregulated Nrf2 and promoted the translocation of Nrf2 from cytoplasm to the nuclei. Additionally, SCE significantly suppressed the expression of cytosolic Kelch-like ECH-associated protein 1 (the repressor of Nrf2) and remarkably increased Nrf2 stability in HepG2 cells. Taken together, our findings suggest that the hepatoprotective effects of SCE may be partially ascribed to the modulation of DMEs and drug transporters via Nrf2-mediated signaling pathway. SCE may alter the pharmacokinetics of other coadministered drugs that are substrates of these DMEs and transporters and thus cause unfavorable herb–drug interactions. Keywords: Nrf2, Keap1, HepG2 cell, drug metabolizing enzyme, drug transporter, P-gp, MRP, OATP, Schisandra chinensis